Developing a measure of intrapreneurial self-efficacy (ISE): assessing employees’ confidence in their ability to create improvements at work - Warren, Chi-Leigh (My University, 2025)
This thesis develops and validates an intrapreneurial self-efficacy (ISE) scale. There are two overarching goals of this study: first, to clarify and improve the construct validity of intrapreneurship (often operationalized with behavior) and subsequently, intrapreneurial selfefficacy (or one’s confidence in performing intrapreneurial behavior), with a definitional analysis, and second, to develop an improved, reliable, validated measure of intrapreneurial selfefficacy that demonstrates discriminant validity from other self-efficacy measures and predicts individual-level intrapreneurial behavior. Referencing a proposed model of intrapreneurship by Neessen et al. (2019), this study further clarifies the construct of intrapreneurship and addresses key gaps in the literature by connecting individual-level attitudes of intrapreneurship, such as ISE, to individual-level intrapreneurial behavior. RQ1: Does intrapreneurial self-efficacy have five subdimensions: innovativeness, proactiveness, risk-taking, opportunity recognition, and networking? A definitional analysis was conducted first to clarify the intrapreneurship construct and inform the writing of the 72 items in the initial item pool, which was evaluated and reduced by subject matter experts (SMEs) to 40 items. Using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA), the scale’s factor structure was explored and confirmed with a 36-item measure. To test H1 and H2, factor-level second-order CFA models assessed for discriminant validity of ISE to identify if it was a unique measure from entrepreneurial self-efficacy (ESE) and general self-efficacy (GSE). H1: Intrapreneurial self-efficacy (ISE) will account for unique model variance, suggesting it is a unique construct from entrepreneurial self-efficacy (ESE). H2: Intrapreneurial self-efficacy (ISE) will account for unique model variance, suggesting it is a unique construct from general self-efficacy (GSE). Finally, hierarchical regression models predicting intrapreneurial behavior were used to test H3 and the criterion-related validity of intrapreneurial self-efficacy as additional variables were added. H3: Intrapreneurial self-efficacy (ISE) will be a positive, significant predictor intrapreneurial behavior above and beyond entrepreneurial self-efficacy (ESE) and general selfefficacy (GSE). ISE was found to be a 5-factor model with 36 items that uniquely predicts intrapreneurial behavior from GSE and ESE. ISE remained a positive, strong, and significant predictor of intrapreneurial behavior even after controlling for GSE, ESE, personality, job attitudes (job satisfaction and prior knowledge of intrapreneurship), and organizational factors (such as work discretion, time available, management support, and rewards/reinforcement). This study refines the construct of ISE and intrapreneurship, develops an improved ISE measure, and investigates the discriminant and criterion-related validity of intrapreneurial selfefficacy, finding support that ISE is unique from ESE and GSE as both a construct and predictor of intrapreneurial behavior.
Keywords: Intrapreneurship; Entrepreneurship; Innovation; Individual differences; Scale development; Psychometrics